Contemporary vision in philosophy and education (Journal of the College of Basic Education, 2023)
This research aims to provide a contemporary vision in two basic fields of knowledge.Humanities are: philosophy and education, and to present a contemporary vision in any field of knowledge.It means an attempt to present a new understanding and interpretation that differs from the previous visions in the ages.There is no doubt that such an attempt will be of great importance in philosophical studies.and contemporary education. The research included presenting the vision of the era in philosophy in the research.The first, which dealt with the limits and possibilities of philosophy, the foreclosed, and the specificity of philosophical criticism.Contemporary, and then presenting the contemporary vision in the philosophy of education in the second topic, whichIt deals with the philosophy of education in its eras and trends represented in the ideal and realistic direction.and pragmatic, and cyber, and the research was chosen on the philosophy of the educational process in the cyber worldPresses.